A tale of three pandemics: Shining a light on a hidden problem. Issue 4 (August 2022) - Graham, Simon Matthew; Laubscher, Maritz; Lalloo, David G.; Harrison, William James; Maqungo, Sithombo
Abstract: An "epidemic" is an event in which a disease, infectious or non-infectious, is actively spreading within a population and designated area. The term "pandemic" is defined as "an epidemic occurring worldwide, or over a very wide area, crossing international boundaries and usually affecting a large number of people". The global response to the COVID-19 pandemic has not been seen since the outbreak of Human Immunodeficiency Virus in the early eighties. But there is another unseen pandemic running alongside the current COVID-19 pandemic, which affects a vast number of people, crossing international boundaries and occurring in every single country worldwide. The pandemic of traumatic injuries. Traumatic injuries account for 11% of the current Global Burden of Disease, resulting in nearly 5 million deaths annually and is the third-leading cause of death worldwide. For every trauma-related death, it is estimated that up to 50 people sustain permanent or temporary disabilities. Furthermore, traumatic injuries occur at disproportionately higher rates in low- and middle-income countries, with approximately 90% of injuries and more than 90% of global deaths from injury occurring these countries. Injuries are increasing worldwide, crossing international boundaries and affecting a large number of people, in the same manner Human Immunodeficiency Virus did in the 1980's and COVID-19 is today. The tremendous global effort to tackle the COVID-19 and Human Immunodeficiency Virus pandemics has occurred whilst ignoring the comparable pandemic of injury. Without change and future engagement with policy makers and international donors this disparity is likely to continue. Highlights: The global response to the COVID-19 pandemic has not been seen since the outbreak of Human Immunodeficiency Virus in the early eighties. There is another unseen pandemic which affects a vast number of people, crossing international boundaries and occurring in every single country worldwide - injury. Traumatic injuries account for 11% of the current Global Burden of Disease (GBD), resulting in nearly 5 million deaths annually and is the third-leading cause of death worldwide. They occur at disproportionately higher rates in low- and middle-income countries. Without change and future engagement with policy makers and international donors this disparity is likely to continue.